Human resource planning for authorized inspection activity - Seung-hee Lee; Robert Murray Field (Nuclear Engineering and Technology, 2019)
When newcomer countries consider a nuclear power programme, it is recognized that the most important organizations are the Nuclear Energy Programme Implementing Organization (NEPIO), the regulator, and an operating organization. Concerning the number of construction delays these days, one of the essential organizations is an Authorized Inspection Agency (AIA). According to World Nuclear Industry Status Report, all of the reactors under construction in eight out of the thirteen countries have experienced delays. Globally, the Flamanville 3 project and Sanmen Unit 1 are 6.5 years and 5 years late respectively. One of the major reasons of delay is due to inappropriate manufacturing and inspection on safety class components.The recommendations are made to develop such an organization: (i) find existing inspection organizations in relevant industries, (ii) contract with expatriates who have experience on nuclear inspection, (iii) develop a legislative framework to authorize the inspection organization with enforcement, (iv) include a contract clause in the BIS for developing the AIA, (v) hold training programmes from vendor country, (vi) during manufacturing and construction, domestic AIA shall be involved. Keywords: Authorized inspection agency, AIA, Nuclear inspection, Authorized nuclear inspection, ANI, Human resource for nuclear inspection